2020
DOI: 10.3390/genes11101217
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in the 14-α Sterol Demethylase Cyp51A or Cyp51C Could Contribute to Azole Resistance in Aspergillus flavus

Abstract: Infections caused by Aspergillus species are being increasingly reported. Aspergillus flavus is the second most common species within this genus causing invasive infections in humans, and isolates showing azole resistance have been recently described. A. flavus has three cyp51-related genes (cyp51A, cyp51B, and cyp51C) encoding 14-α sterol demethylase-like enzymes which are the target of azole drugs. In order to study triazole drug resistance in A. flavus, three strains showing reduced azole susceptibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The mechanisms causing triazole resistance in A. flavus are less well characterised. However, recent studies have identified a number of azole resistant isolates and documented Cyp51A, Cyp51B or Cyp51C target enzyme alterations [ 24 , 25 , 26 , 27 , 28 ], upregulation of target gene expression [ 26 , 29 ], or efflux pump upregulation [ 26 , 29 , 30 ] in the resistant isolates. Moreover, resistance has been suggested among environmental A. flavus isolates in Vietnam [ 31 ] and Argentina [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms causing triazole resistance in A. flavus are less well characterised. However, recent studies have identified a number of azole resistant isolates and documented Cyp51A, Cyp51B or Cyp51C target enzyme alterations [ 24 , 25 , 26 , 27 , 28 ], upregulation of target gene expression [ 26 , 29 ], or efflux pump upregulation [ 26 , 29 , 30 ] in the resistant isolates. Moreover, resistance has been suggested among environmental A. flavus isolates in Vietnam [ 31 ] and Argentina [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al showed that a T788G mutation in the CYP51C gene was responsible for voriconazole resistance in A. flavus . However, Paul et al contradicted this conclusion because this mutation was not found in their strains and another mutation (Y319H) has been highlighted and implicated in mediating voriconazole resistance [ 29 , 30 , 31 ]. CYP51A protein sequences from our panel of FSSC strains have been compared to other complexes in the genus Fusarium .…”
Section: Methodsmentioning
confidence: 99%
“…In humans, Aspergillus flavus is one of genus causing invasive infections. A. flavus has CYP51A, CYP51B, and CYP51C genes which are the target of azole drugs [67]. The result of gene expression analysis showed that CYP51A and CYP51B expression levels were greater than that of CYP51C.…”
Section: Fungal P450 As An Antifungal Drug Targetsmentioning
confidence: 99%